Anticancer activity of large metalla-assemblies built from half-sandwich complexes. Issue 26 (2nd March 2016) - Gupta, Gajendra; Oggu, Gopi Suresh; Nagesh, Narayana; Bokara, Kiran Kumar; Therrien, Bruno
Abstract : A series of octanuclear p -cymene ruthenium and pentamethylcyclopentadienyl rhodium and iridium metalla-assemblies has been prepared from tetrapyridyl porphyrin panels. All assemblies possess IC50 values around 0.1 μM, and induce apoptosis in cancer cells. Abstract : A series of octanuclear p -cymene ruthenium and pentamethylcyclopentadienyl rhodium and iridium metalla-assemblies has been prepared from tetrapyridyl porphyrin (tpp) panels and the corresponding dinuclear clips, (η 6 -MeC6 H4 Pr i )2 Ru2 (μ4 -C6 HRO4 )Cl2 (R = C11 H23 ) and (η 5 -C5 Me5 )2 M2 (μ4 -C6 HRO4 )Cl2 (M = Rh, Ir). All complexes were isolated in good yield as their triflate salts, [(η 6 -MeC6 H4 Pr i )8 Ru8 (μ4 -tpp)2 (μ4 -C6 HRO4 )4 ][CF3 SO3 ]8 (1 ), [(η 5 -C5 Me5 )8 Rh8 (μ4 -tpp)2 (μ4 -C6 HRO4 )4 ][CF3 SO3 ]8 (2 ) and [(η 5 -C5 Me5 )8 Ir8 (μ4 -tpp)2 (μ4 -C6 HRO4 )4 ][CF3 SO3 ]8 (3 ), and fully characterized by spectroscopic methods. The antiproliferative activity of the complexes was evaluated on the cancerous (MCF-7, B16 and A549) and non-cancerous (NIH 3T3) cell lines, showing in all cases IC50 values around 0.1 μM. Further biological studies suggest that apoptosis is induced by the complexes and that interaction with DNA can be in part responsible for the high cytotoxicity.